Incidental gastric glomus tumor after laparoscopic sleeve gastrectomy - Oruç, Mehmet Tahir; Çakir, Tuğrul; Aslaner, Arif; Çekiç, Sema; Sakar, Alkan; Yardimci, Erdem Can (Autopsy and Case Reports, 2016)
Gastric glomus tumors (GGTs) are unusual benign, subepithelial, mesenchymal neoplasms of modified smooth muscle cells representing a neoplastic counterpart of glomus bodies. A 38-year-old woman was admitted to our clinic presenting morbid obesity. Routine preoperative evaluations, such as laboratory analysis, abdominal ultrasonography, and upper gastrointestinal endoscopy, were performed. She underwent a classical laparoscopic sleeve gastrectomy (LSG). The postoperative course was uneventful and she was discharged for outpatient control. Her histopathology report revealed a GGT 0.8 cm in diameter. No further treatment was done and she had lost 28 kg at the postoperative sixth month. Here, we present the case of GGT, which was diagnosed incidentally after LSG